2018
DOI: 10.1002/ecs2.2303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forest management on temperate ant communities

Abstract: Human management of ecosystems can have direct or indirect effects on species communities. How species communities are affected by management is a key question in ecology and nature conservation. As keystone taxon, changes in ant communities can have sustained consequences for entire ecosystems. In forests, management has been shown to have an overall negative effect on ant communities in tropical and a positive effect in boreal forests. However, in temperate forests, it is unclear what components of forest ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 83 publications
3
17
0
Order By: Relevance
“…A study on leaf litter ants in the same experiment revealed positive correlations between tree species richness and ant abundance, species richness and phylogenetic diversity [61••], indicating that the "enemies" hypothesis can apply to forest-floor organisms that do not directly interact with trees. A positive effect of tree species richness on ant species richness was also observed in species poor, managed forests in temperate Europe, although effects were weaker than those of tree species identity [62].…”
Section: Predatory Antsmentioning
confidence: 80%
“…A study on leaf litter ants in the same experiment revealed positive correlations between tree species richness and ant abundance, species richness and phylogenetic diversity [61••], indicating that the "enemies" hypothesis can apply to forest-floor organisms that do not directly interact with trees. A positive effect of tree species richness on ant species richness was also observed in species poor, managed forests in temperate Europe, although effects were weaker than those of tree species identity [62].…”
Section: Predatory Antsmentioning
confidence: 80%
“…[12]), SCI can be calculated from conventional inventory data. Both have proven useful in the past as surrogates of microclimatic stability (SSCI; [41]), classifiers of forest types (SCI: [23]; SSCI: [12] and [35]), or predictors of biodiversity, e.g., for ant species (SSCI: [51]) or tree species diversity (SSCI: [12]). Here, the birds-eye perspective of airborne laser scanning (ALS) yielded intermediate but significant correlations (R = 0.35 − 0.51) between D b and the two ground-based measures of structural complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Pastures in the Schorfheide were never grazed by sheep, which was where high ant species richness was found in the Alb and Hainich. Recently, Grevé et al () showed that forest plots at the Schorfheide are rather dry and species‐rich, which implies a potentially large regional species pool. This suggests that a potential increase of ant species richness in grassland plots could be achieved by a change in the grassland management, shifting from cattle to sheep pastures.…”
Section: Discussionmentioning
confidence: 99%